Peranan Saksi Mahkota Dalam Perkara Tindak Pidana Kasus Pembunuhan Berencana Brigadir Joshua Dikaitkan Dengan Asas Non Self Incrimination - Bambang Sukarjono; Meirza Aulia Chairani; Angga Pramodya Pradhana; Lusi Ardiani (Universitas Merdeka Madiun, 2023)
Abstract-The purpose of this study was to analyze the role of the crown witness in the premeditated murder case of Brigadier Joshua associated with the principle of non-self-incrimination and the obstacles to using a crown witness in the premeditated murder case of Brigadier Joshua associated with the principle of non-self-incrimination. This writing research method uses a normative juridical method with three approaches, namely the statutory approach (statute approach), conceptual approach (conceptual approach), and case approach (case approach). The results of the research on the role of the crown witness in the premeditated murder case of Brigadier Joshua were linked to the principle of non-self-incrimination, there were five defendants who were used as crown witnesses against the other defendants namely Ferdy Sambo, Putri Candrawathi, Bripka Ricky Rizal, Strong Ma'ruf and Bharada E However, there were two defendants who refused to be the crown witness for the other defendant, namely Ferdy Sambo who refused to be a witness for Putri Candrawathi, and vice versa Putri Candrawathi refused to be a witness for Ferdy Sambo. With this in mind, there are obstacles that come from obstacles to the defendant, obstacles to evidence, and obstacles to the trial judge. Based on this study, the use of crown witnesses in court proceedings is common. Aims to open the veil of crime from the defendant who was used as a witness. However, the use of crown witnesses must still pay attention to the human rights of the accused. In criminal law theory, this provision is referred to as the principle of non-self-incrimination, namely the defendant has the right not to provide information that incriminates himself (privilege against self-incrimination), which in practice the attitude of silence and not admitting to the accused is used as an excuse or circumstance that can be aggravating for punishing the accused.